INCOME ANALYSIS OF RICE FARMING BUSINESS (ORYZA SATIVA L.)(Case Study: Legal Sustainable Gapoktan in Sukaresmi Village, District Megamendung, Bogor Regency, West Java Province) - Isma Mutiara Anisa (Agripreneur : Jurnal Pertanian Agribisnis, 2022)
Rice is one of the food crop commodities that produce rice. Most of Indonesia's population make rice as a staple food everyday. The purpose of this study was to calculate the farming costs incurred by rice farmers from Gapoktan Official Lestari, to analyze the income of rice farmers from Gapoktan Official Lestari, to analyze the feasibility of farming rice farmers from Gapoktan Official Lestari using B/C ratio, Break Event Point (BEP). ), Payback Period (PP). This was done to the Gapoktan Official Lestari farmers who did rice farming with a total population of 30 respondents. The data used in this study are primary data and secondary data. The collected data were analyzed qualitatively and quantitatively which were processed using Microsoft Excel. Qualitative data analysis using descriptive analysis was carried out to describe the rice farming activities of the Gapoktan Official Lestari. While the analysis of quantitative data uses income analysis to calculate the costs incurred and income earned on paddy rice farming Gapoktan Official Lestari.